Neural pathway of bellows response during SNM treatment revisited: Conclusive evidence for direct efferent motor response. Issue 5 (2nd June 2020) - Vaganée, Donald; Voorham, Jeroen; Panicker, Jalesh N.; Fransen, Erik; Voorham‐van der Zalm, Petra; Van de Borne, Sigrid; De Wachter, Stefan
Abstract: Background: In sacral neuromodulation (SNM) patients, it is thought the bellows response elicited upon sacral spinal nerve stimulation is reflex‐mediated. Therefore the mechanism of action of SNM is considered to be at the spinal or supraspinal level. These ideas need to be challenged. Objective: To identify the neural pathway of the bellows response upon sacral spinal nerve stimulation. Design, Setting, and Participants: Single tertiary center, prospective study (December 2017‐June 2019) including 29 patients with overactive bladder refractory to first‐line treatment. Intervention: Recording of the pelvic floor muscle response (PFMR) using a camcorder and electromyography (EMG) (intravaginal probe and concentric needles) upon increasing stimulation during lead or implantable pulse generator placement. Outcome Measurements and Statistical Analysis: The lowest stimulation intensity needed to elicit a visual PFMR and electrical PFMR was determined. Electrical PFMRs were subdivided according to their latency. Outcome: the association between visual and electrical PFMRs. Statistical analyses were performed using the weighted kappa coefficient. Results: Three different electrical PFMRs could be identified by surface and needle EMG, corresponding with a direct efferent motor response (R1), oligosynaptic (R2), and polysynaptic (R3) afferent reflex response. Only the R1 electrical PFMR was perfectly associated with the visual PFMR ( κ  = 0.900). Conclusions: The visual PFMRs upon sacral spinal nerve stimulation are direct efferent motor responses. A reopening of the discussion on the mechanism of action of SNM is possibly justified.